Artificial Intelligence for Thyroid Disorders: A Systematic Review - Al Hakim, Rosyid Ridlo; Satria, Muhammad Haikal; Arief, Yanuar Zulardiansyah; Setiawan, Antonius Darma; Pangestu, Agung; Hidayah, Hexa Apriliana (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
The thyroid gland plays a very important role in hormonal regulation in the human body. If the thyroid gland has a disorder, it can affect the performance of body functions. The development of artificial intelligence technology today allows an expert such as a doctor to be helped by his work. One of the important roles of artificial intelligence is helping doctors, among others, to diagnose a patient to determine appropriate post-diagnosis care. The study aims to shed light on the role of artificial intelligence in the treatment of thyroid disorders.The thyroid gland plays a very important role in hormonal regulation in the human body. If the thyroid gland has a disorder, it can affect the performance of body functions. The development of artificial intelligence technology today allows an expert such as a doctor to be helped by his work. One of the important roles of artificial intelligence is helping doctors, among others, to diagnose a patient to determine appropriate post-diagnosis care. The study aims to shed light on the role of artificial intelligence in the treatment of thyroid disorders.